Use of Laryngeal Mask and Anesthetic Management in Hamadryas Baboons (Papio hamadryas) Undergoing Laparoscopic Salpingectomy—A Case Series - Annalaura Scardia; Pietro Laricchiuta; Marzia Stabile; Claudia Acquafredda; Luca Lacitignola; Annamaria Uva; Antonio Crovace; Francesco Staffieri (Veterinary Sciences, 2023)
The study aims to describe the anesthetic and airway management of baboons (Papio hamadryas) undergoing laparoscopic salpingectomy with a laryngeal mask airway (LMA) device. Eleven baboons received tiletamine-zolazepam and medetomidine; anesthesia was induced with propofol. An LMA was positioned for oxygen and isoflurane administration in spontaneous respiration. Heart rate (HR), mean arterial pressure (MAP), respiratory rate (RR), end tidal carbon dioxide (EtCO2), minute volume (MV), and peripheral hemoglobin oxygen saturation (SpO2) were recorded before (PREPP) and immediately after abdomen insufflation (PP1), at 10 (PP2), 20 (PP3), and 30 (PP4) minutes during pneumoperitoneum, and after (POSTPP) pneumoperitoneum. The respiratory rate was significantly higher at all times compared to PREPP. The end tidal carbon dioxide concentration was significantly higher at PP2, PP3, PP4, and POSTPP, compared to the previous times. The higher values for RR and EtCO2 were registered at PP4: 22.7 (95% CI 17.6–27.8) breaths/min and 57.9 (95% CI 51.9–63.8) mmHg, respectively. The minute volume was significantly higher at PP4 and POSTPP compared to the other times. The higher value for MV was registered at POSTPP (269.1 (95% CI 206.1–331.8) mL/kg/min). This protocol is suitable for baboons undergoing laparoscopic salpingectomy. The LMA was easy to insert and allowed for good ventilation, gas exchange, and delivery of the anesthetic in spontaneous breathing baboons.